Implementation of An Integrated Referral System (Sisrute) In Improving Health Service Referrals at Rumah Sakit Umum Pusat (RSUP) H. Adam Malik Medan - Zulharryansah Mesir Siregar; Rangkuti, Zoraya Alfathin (Journal of Law, Politic and Humanities, 2024)
The Integrated Referral System (SISRUTE) is a service using internet-based information technology that can connect patient data from lower service levels to higher or equivalent service levels (horizontal or vertical) with the aim of simplifying and speeding up the patient referral process. Rumah Sakit Umum Pusat (RSUP) H. Adam Malik Medan is one of the hospitals that has implemented SISRUTE, namely in 2021. The method used in this study is a descriptive method with a qualitative approach. The data collection techniques are interviews, observations and documentation. The results showed that the Implementation of the Integrated Referral System (SISRUTE) in Improving Health Referral Services at H. Adam Malik Hospital Medan City is still not optimal seen from the miscommunication that occurs between regional hospitals and hospitals in Medan City. Furthermore, the resource parameters include human resources who run the Integrated Referral System (SISRUTE) at H. Adam Hospital Medan City is still not optimal because there is still a lack of BIMTEK training conducted by the Ministry of Health of the Republic of Indonesia (KEMENKES) and facilities and infrastructure resources are also still limited at H. Adam Malik Hospital Medan City. The disposition in the form of executive commitment can be improved for the better.